A battery composite interface layer and a preparation method and application thereof

CN122992069APending Publication Date: 2026-10-27SHENZHEN UNIVERSITY OF ADVANCED TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611164958.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]针对现有技术中的缺陷,本发明提出了一种电池复合界面层及其制备方法和应用,旨在解决固态锂电池在高倍率/高电流密度下容易产生锂枝晶短路、界面接触失效以及电解质化学稳定性差的技术难题,实现了包含复合界面层的电池在超高电流密度下的极低极化运行

Benefits of technology

(1)本发明提供的复合界面层通过“干法金属活性宿主膜”与“纳米级氧化物诱导层”的设计,在界面处诱导生成具有超高离子电导率的富无机相SEI,能够使电池能在0.1mA/cm2-100 mA/cm2的极端电流密度范围内稳定运行,并控制1 mA/cm2下的过电位小于100mV;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992069A_ABST
    Figure CN122992069A_ABST
Patent Text Reader

Abstract

The application discloses a battery composite interface layer and a preparation method and application thereof. The battery composite interface layer comprises a physical buffer layer and a chemical induction layer. The physical buffer layer is a metal active host composite film, which comprises a metal active host material and a polymer binder coated on the surface of the metal active host material. The chemical induction layer is a nanoscale metal oxide film. The metal active host film with the functions of electronic and ion conduction and mechanical buffering is introduced, and the nanoscale passivation layer is combined, so that the long cycle stability of the solid-state battery under extreme working conditions and the extremely low interface polarization are realized. The scheme has strong system universality and can be applied to various systems such as existing polymers, sulfides, halides and oxides.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and in particular to a battery composite interface layer, its preparation method, and its application. Background Technology

[0002] The core bottleneck of all-solid-state batteries (ASSBs) interfaces lies in the failure of physical contact and interfacial instability between the lithium metal anode and the solid electrolyte (SSE). This is the main reason restricting their commercial development, and it includes the following aspects: First, high current dendrite penetration and short circuits can occur. In solid-state batteries, especially solid-state lithium batteries, the solid electrolyte and lithium metal only have a solid-solid point contact. Their wettability is different from that of liquid electrolytes, which easily leads to extremely high interfacial resistance (ASR). In addition, there are microscopic irregularities or pores on the surface of the solid electrolyte. Due to the limited transport kinetics at the interface, lithium ions tend to accumulate and deposit at local high electric fields and be reduced to form lithium dendrites, especially at high current densities (e.g., >10 mA / cm). 2 Under certain conditions, dendrite growth is extremely rapid, easily penetrating along the grain boundaries or pores of the solid electrolyte, leading to thermal runaway or battery short-circuit failure. Secondly, the dynamic volume expansion of lithium metal causes interface desorption and physical failure. Lithium metal undergoes "hostless" deposition / stripping during charging and discharging, resulting in drastic volume changes during repeated insertion and extraction. This easily leads to voids at the interface, causing a continuous reduction in the effective contact area, ultimately resulting in increased battery polarization and failure. This is especially true for rigid solid electrolytes (such as ceramic sheets) which cannot compensate for deformation, making them more prone to interfacial gaps during cycling, leading to an exponential increase in impedance and a shortened cycle life. Thirdly, traditional interface modification processes are destructive to sensitive electrolyte systems. Existing interface treatment methods (such as solution coating and wet slurry modification) typically involve organic solvents, which can cause irreversible performance damage to electrolytes such as sulfides or halides that are highly susceptible to water absorption, decomposition, and swelling. Fourth, various solid-state electrolyte systems exhibit chemical / electrochemical instability with lithium metal. Sulfide and halide electrolytes possess extremely high ionic conductivity, but their electrochemical windows are narrow, and direct contact with metallic lithium easily leads to reduction reactions, generating high-resistivity intermediate phases. Polymer electrolytes (such as PEO) lack sufficient mechanical strength at room temperature and are easily reduced and decomposed by lithium. Most importantly, the cycle performance of existing solid-state batteries faces severe challenges at high current densities. Currently, most interface modification schemes for solid-state batteries in academia and industry typically limit the stable operating current density to 1-5 mA / cm². 2 When the current density is increased to 10 mA / cm 2At the above levels, interfacial kinetic imbalance can induce severe lithium plating and side reactions, making it difficult to meet the requirements for high current density applications. Furthermore, existing interfacial modification schemes often suffer from high brittleness, meaning they cannot withstand the repeated and drastic volume expansion and contraction of lithium metal during ultra-long charge-discharge cycles (e.g., >2000 h). This can lead to microcracks or even peeling of the interfacial layer, causing the solid electrolyte to be re-exposed and react directly with the lithium metal, making it difficult to withstand currents such as 100 mA / cm². 2 The extreme operating conditions and the fact that most interface layers currently use slurry coating methods (wet methods) make it difficult to completely remove the polar organic solvents (such as NMP and DMF) used in these methods. The residual solvents will continue to undergo electrochemical decomposition at the highly reducing lithium metal interface, generating gas and forming an unstable organic phase SEI, which leads to a continuous increase in internal resistance. In addition, the traditional binders used in existing solutions do not have ion conduction capabilities and are difficult to induce the generation of high-performance inorganic SEI components during cycling. Furthermore, the existing solutions are highly specific. Modification layers that are effective for oxide electrolytes may fail in sulfide systems due to chemical incompatibility, or solutions that are effective for polymers may fail to establish good physical contact in halide electrolytes, which is also one of the defects of existing interface modifications. In addition, the low utilization rate of active materials and incomplete phase transformation of traditional interfaces can also lead to poor battery performance. Due to uneven charge distribution, lithium is deposited unevenly on the lithium active host or lithium metal surface, which limits the actual capacity of the battery.

[0003] Therefore, there is an urgent need to develop a novel anode interface optimization technology for solid-state batteries, enabling the batteries to adapt to ultra-high rate ranges and cope with 100 mA / cm². 2 It can operate stably under high current density and meet the requirements of ionic conductivity, mechanical toughness and chemical stability of the interface layer. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention proposes a battery composite interface layer, its preparation method, and its application. It aims to solve the technical problems of lithium dendrite short circuits, interface contact failures, and poor electrolyte chemical stability in solid-state lithium batteries at high rates / high current densities. The invention achieves extremely low polarization operation of batteries containing the composite interface layer at ultra-high current densities.

[0005] This invention provides a battery composite interface layer, which includes a physical buffer layer and a chemical induction layer;

[0006] The physical buffer layer is a metal active host composite membrane, comprising a metal active host material and a polymer binder coated on its surface. The physical buffer layer has a micro three-dimensional network fiber skeleton formed by fibrillation of the binder. The fiber diameter is 10 nm-5000 nm. The active host material particles are anchored by the fiber skeleton and are uniformly distributed in the composite membrane. The chemically induced layer is a nanoscale metal oxide thin film; The metal active host material is any one or more of graphite, graphene, silicon suboxide, molybdenum dioxide, conductive carbon black, hard carbon, and carbon nanotubes. When graphite is combined with any one of graphene, silicon suboxide, molybdenum dioxide, conductive carbon black, hard carbon, and carbon nanotubes, the composite ratio is (70-99):(1-30). The nanoscale metal oxides are oxides of metal elements from Group IIIA, Group IIB or Group IVB of the periodic table.

[0007] Furthermore, the polymer binder is a fibrillable polymer binder, which is selected from any one or more of fluorinated polymer materials, aramid fibers, or polyimides.

[0008] Further, the polymer binder is polytetrafluoroethylene, perfluoroalkyl compounds, fluorinated ethylene-propylene copolymers, ethylene-tetrafluoroethylene copolymers, polyvinylidene fluoride, preferably a fluorinated polyolefin polymer, and more preferably, the polymer binder comprises polymers with a weight average molecular weight of 10. 6 -10 7 Fluorinated polyolefin polymers.

[0009] Furthermore, the thickness of the physical buffer layer is 5-50 μm.

[0010] This invention introduces a metal active host film (active host material + fibrillable polymer binder) that combines electronic and ion conduction with mechanical buffering functions, transforming metal deposition from "point-to-point" contact to "surface conduction." Furthermore, it establishes a uniform rectification layer of nanoscale oxide film at the interface, fundamentally suppressing dendrite growth and enabling the battery to withstand speeds up to 100 mA / cm². 2This invention achieves extreme current densities without short-circuiting. Utilizing an ultrathin metal active host film as an interface buffer layer, its viscoelastic and lamellar sliding properties provide mechanical support and stress release space for the interface, maintaining tight physical contact throughout 5000 hours of long-term cycling. Furthermore, this invention combines a nanoscale metal oxide passivation layer with the metal active host film, achieving long-term cycling stability and extremely low interfacial polarization of the solid-state battery under extreme conditions. By constructing a nanoscale oxide film in situ on the electrolyte surface, this film also serves as an artificial solid electrolyte interface, physically isolating the electrolyte from lithium metal, effectively widening the electrochemical stability window of the electrolyte, and preventing the continuous increase in impedance caused by side reactions.

[0011] This invention achieves for the first time the synergistic design of ultrathin metal active host / membrane and nano-oxide thin film, combining dry fibrillation technology with thin film deposition technology, and solving the problem of balancing "kinetics, stability, and mechanical properties" in existing technologies. Existing solutions achieve greater than 10 mA / cm 2 Short circuits often occur at current densities of 100 mA / cm², while this invention achieves short circuits at 100 mA / cm². 2 Even at current densities of 1 mA / cm², it will not experience short circuits and can cycle stably for over 2000 hours, even exceeding 5000 hours. Furthermore, the battery of this invention, containing a composite interface layer, exhibits ultra-low polarization at 1 mA / cm². 2 The overpotential of less than 100mV at the current density proves that the inorganic-rich SEI (LiF, Li3N, Li2S, Li2O, etc.) generated at the interface provides extremely high ion migration rates, which are far superior to traditional schemes.

[0012] Furthermore, by selecting active host materials, the specific capacity of the interface can be further improved.

[0013] Furthermore, the mass ratio of the metal active host material to the polymer binder is (9-199):1.

[0014] Furthermore, the nanoscale metal oxide is any one of Al2O3, ZnO, ZrO2, TiO2, HfO2, MgO, SiO2, LiNbO3, LiTaO3, Li3PO4, or LiPON.

[0015] Furthermore, the thickness of the composite interface layer is 1-100 μm, preferably 10-30 μm. By controlling the thickness of the composite interface layer, thinner micro batteries or batteries that meet the requirements for long lifespan can be obtained.

[0016] Furthermore, the thickness of the nanoscale metal oxide film is 0.5-10 nm.

[0017] Furthermore, the interface mechanism of the composite interface layer of the present invention can be characterized by XPS and TOF-SIMS electron microscopy; the phase transformation can be characterized by XRD patterns; and the stability of the interface phase can be tested by SEM.

[0018] The present invention also provides a method for preparing the composite interface layer, including any one of the following two preparation methods: (1) dry premixing the metal active host material with the polymer binder and performing shear fibrillation treatment to make the mixture fibrillated, and then performing a warm rolling process to obtain a metal active host composite film, and depositing a nanoscale metal oxide film on the surface of the composite film to obtain the composite interface layer. (2) The metal active host material is premixed with the polymer binder and subjected to shear fibrillation treatment to make the mixture fibrillated. Then, the metal active host composite membrane is obtained by warm rolling process. A nanoscale metal oxide film is deposited on the surface of the solid electrolyte membrane. Then, the metal active host composite membrane and the solid electrolyte membrane with the deposited nanoscale metal oxide film are rolled together to obtain the composite interface layer.

[0019] By selecting the preparation method, it is possible to design a metal active host membrane with gradient porosity or gradient fluorine content, and control the fluorine content to be higher on the side closer to the electrolyte to enhance the enrichment of LiF.

[0020] Furthermore, the warm rolling process is a multi-stage warm rolling process, wherein the roll surface temperature is 20℃-90℃, the roll pressure is 100 kg / cm-50000 kg / cm, and the single-pass reduction rate during the roll rolling process is 1%-30%. The dry metal active host film prepared by the precision roll rolling process has a uniform thickness, is easy to produce on a large scale roll to roll, and the process is solvent-free. Compared with the wet process, there is no solvent evaporation during the production process, which proves the industrial application potential of the dry process.

[0021] Furthermore, the deposition can be selected from any one of atomic layer deposition (ALD), chemical vapor deposition (CVD), physical vapor deposition (PVD), magnetron sputtering, electron beam evaporation, plasma-enhanced deposition (PECVD), wet spraying, spin coating, and immersion.

[0022] Furthermore, the nanoscale metal oxide film is prepared by atomic layer deposition (ALD) process, specifically including using an organometallic compound as a metal source precursor and deionized water (H2O) as an oxygen source precursor. A single ALD cycle includes four stages: metal source precursor pulse (TMA), residual gas purging, H2O pulse, and residual gas purging. The TMA pulse time is 0.01 s-2 s, the H2O pulse time is 0.01 s-1.5 s, and the purging stage uses high-purity nitrogen or argon as the carrier gas, with a single purging time of 5 s-60 s.

[0023] Furthermore, the atomic layer deposition (ALD) process involves controlling the deposition chamber temperature at 30℃-150℃, maintaining a vacuum level at 0.001-10 Torr, a carrier gas flow rate at 10 sccm-300 sccm, controlling the number of circulation cycles at 2-200, and achieving a deposition thickness of 0.1-20 nm, thereby achieving conformal coating on the surface of active host particles or electrolytes.

[0024] This invention employs a completely dry method to prepare a self-supporting metal active host membrane and combines it with deposition technology to obtain nanoscale metal oxide thin films. The entire modification process does not use solvents, achieving compatibility with electrolytes of all systems, including polymers, sulfides, oxides, and halides. It has extremely high industrial versatility and can be applied to various existing systems such as polymers, sulfides, halides, and oxides.

[0025] The present invention also provides the application of the composite interface layer in all-solid-state batteries, liquid batteries or semi-solid-state batteries. In addition to all-solid-state batteries / semi-solid-state batteries, the metal active host film of the present invention can also be used as an artificial SEI protective film for metal anodes in traditional liquid electrolyte batteries to solve the problems of severe lithium dendrite formation and easy cracking of organic SEI in liquid systems.

[0026] The present invention also provides an all-solid-state battery, comprising a metal negative electrode, a solid electrolyte, and the aforementioned composite interface layer disposed between the two.

[0027] Furthermore, the all-solid-state battery is any one of solid-state lithium metal battery, solid-state sodium metal battery, solid-state magnesium metal battery, and solid-state potassium metal battery. By adjusting the composition of the induction layer, the corresponding interface phases such as LiF, Li3N, or NaF, Na3N are induced to be generated.

[0028] Furthermore, the chemically induced layer in the composite interface layer is a nanoscale metal oxide film with a thickness of 0.5 nm to 10 nm, formed by a thin film deposition process and located on the surface of a self-supporting metal active host film or a solid electrolyte.

[0029] Furthermore, the chemically induced layer in the composite interface layer can be deposited on both sides. It can be deposited not only on the surface of the solid electrolyte, but also on the surface of the dry lithium active host film, forming a multi-level induced structure of "lithium metal | lithium active host film | nanoscale metal oxide film | electrolyte".

[0030] The composite interface layer provided by this invention is particularly suitable for composite interface modification layers in all-solid-state batteries. It involves constructing a lithium active host / fibrillable polymer binder film prepared by a dry process between the solid electrolyte powder / electrolyte film and the lithium metal anode. Furthermore, a nanoscale oxide layer (oxide, tin oxide, etc.) is introduced onto the solid electrolyte surface through atomic layer deposition or physical / chemical deposition processes. Utilizing the catalytic guiding effect of the oxide on the interfacial reduction reaction and the fluorinated chemical environment provided by the fibrillable polymer binder network, an inorganic-rich solid electrolyte interface (SEI) layer with core components such as LiF and Li3N is induced in situ during charge-discharge cycles. This effectively reduces the lithium-ion desolvation energy barrier and migration impedance. The lithium active host dry film framework absorbs the volumetric stress generated by lithium deposition, and the lithium active host particles can be deeply and stably transformed into a high-lithium-content, iso-ion-conducting phase after repeated lithium insertion / extraction. The resulting composite interface layer exhibits excellent electrochemical and kinetic performance, enabling lithium-lithium symmetric batteries to operate at speeds of 0.1-100 mA / cm². 2 It can cycle stably for more than 5000 hours without short circuit within a wide current density range, at 1 mA / cm². 2 The interfacial polarization overpotential is less than 100 mV, and it exhibits broad applicability to solid electrolytes of all systems, including polymers, sulfides, halides and oxides.

[0031] In summary, compared with the prior art, the present invention achieves the following technical effects: (1) The composite interface layer provided by the present invention, through the design of "dry metal active host film" and "nanoscale oxide induction layer", induces the generation of an inorganic-rich SEI with ultra-high ionic conductivity at the interface, enabling the battery to achieve a conductivity of 0.1 mA / cm 2 -100 mA / cm 2 It operates stably within the extreme current density range and is controlled at 1 mA / cm². 2 The overpotential is less than 100mV; (2) The composite interface layer provided by the present invention constructs a self-supporting interface buffer layer with high mechanical toughness: by utilizing the fibrillation characteristics of fibrillable polymer binders, a self-supporting metal active host composite membrane with a three-dimensional fiber network is constructed. By utilizing the flexibility and thickness advantages of this layer, the volume stress during the metal deposition process is effectively absorbed, preventing the interface layer from cracking and ensuring that the battery can achieve an ultra-long stable cycle of more than 5000 h without short circuit. (3) The composite interface layer provided by the present invention can eliminate the pollution of residual solvents and side reactions at the interface. Through the dry preparation process, the use of organic solvents is completely eliminated. It does not combine the pure physical mixing and rolling process to build a "clean" interface environment and eliminate the gas evolution and side reaction problems caused by residual solvents from the source. (4) The composite interface layer provided by the present invention is a universal interface modification scheme with high versatility. Through the chemical induction effect of the nano oxide layer and the physical compatibility of the dry metal active host film, the purpose is to enable it to be applied to various solid electrolyte systems such as polymers, sulfides, halides, and oxides without discrimination, thereby improving the conversion efficiency and structural stability of active materials. By optimizing the uniform diffusion path of interface ions, it promotes the deep insertion and extraction of lithium ions between lithium active host layers, ensuring that the lithium active host can be completely and stably converted into a high lithium content phase, thereby maximizing the actual usable capacity and coulombic efficiency of the battery. (5) The composite interface layer provided by the present invention can be used not only for metal anodes, but also for cathodes (such as high-voltage lithium cobalt oxide or lithium-rich manganese-based cathodes) as a modified layer of cathode electrolyte interface (CEI), and uses the antioxidant properties of oxides to inhibit the decomposition of electrolytes under high voltage. (6) The high conductivity and high toughness composite interface layer provided by the present invention can be used to prepare electrode materials for supercapacitors and improve the structural stability under high current charging and discharging. Attached Figure Description

[0032] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0033] Figure 1 This is a flowchart illustrating the fabrication process of the composite interface layer of the present invention. Figure 2 This is a schematic diagram of the microstructure of the composite interface layer of the present invention; Figure 3 The limiting current test diagram of Embodiment 1 of the present invention (2-100mA / 1-50mA cm) -2 ); Figure 4 This is a graph from the ultra-high current long-cycle test of Embodiment 1 of the present invention (100mA / 50mA cm). -2 ). Detailed Implementation

[0034] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0035] Example The present invention will be further illustrated below with reference to specific embodiments and comparative embodiments. The following specific embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following embodiments, and are not in particular limited to the types of raw materials used in the following specific embodiments.

[0036] I. The sources of raw materials for the examples and comparative examples are as follows: Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available.

[0037] The method for preparing the composite interface layer in the following embodiments includes the following steps: The metal-active host material and polymer binder are premixed (mass ratio 95:5, which can be adjusted according to different host materials), and then subjected to shear fibrillation treatment to fibrillate the mixture. A warm rolling process is then performed to obtain the metal-active host composite film. A nanoscale metal oxide film is deposited on the surface of the composite film to obtain the composite interface layer. Figure 1 This is a flowchart illustrating the fabrication process of the composite interface layer of the present invention. In the warm rolling process, the roll surface temperature is 20℃-90℃, the roll pressing line pressure is 100 kg / cm-50000 kg / cm, the single-pass reduction rate during the rolling process is 1%-30%, and the thickness of the metal active host composite film is 20-30μm. The deposition is performed using atomic layer deposition, with the deposition chamber temperature controlled at 30℃-150℃, the vacuum level maintained at 0.001-10 Torr, the carrier gas flow rate at 10 sccm-300 sccm, the number of circulation cycles controlled at 2-200, and the deposition thickness at 0.1-20 nm.

[0038] II. Performance Tests (1) Cyclic stability test: The long-cycle performance of the assembled button cells was evaluated using the constant current charge-discharge method and the Xinwei Battery Testing System (the same below).

[0039] (2) Polarization overpotential test: The DC internal resistance method is used for testing.

[0040] (3) Critical current density test: The step current density method is used for testing.

[0041] Table 1. Technical solutions and effects of the embodiments

[0042] The solid-state batteries in Examples 1-7 also introduce specific composite interface layers. Figure 2 This is a schematic diagram of the microstructure of the composite interface layer of the present invention. It can be seen that the composite interface layer comprises a metal-active host composite film composed of a metal-active host material and a polymer binder, as well as a nanoscale metal oxide thin film. The all-solid-state battery obtained by the present invention is not limited by ion migration rate at high current densities, and the critical current density (CCD) can be significantly improved. The present invention utilizes a metal-active host material + fibrillable polymer binder and electrolyte decomposition to generate an SEI film with high ionic conductivity at the interface. For example, for lithium batteries, Li3N and LiF can be formed at the interface, as well as a high-lithium-content phase generated after lithium intercalation in the metal-active host. This inorganic-phase-rich interface can achieve 1 mA / cm² conductivity. 2 The overpotential is reduced to below 100 mV, supporting stable battery operation at high current densities. Furthermore, parallel experiments were conducted on four major types of solid electrolytes (sulfides, halides, polymers, and oxides). The test results show that no short circuits occurred in any of the systems, and the performance improvement was highly consistent.

[0043] Among them, the interface modified in Example 1 can operate stably over an extremely wide current density range of 0.1 mA / cm² to 100 mA / cm² (e.g. Figure 3 ),like Figure 4 In long charge-discharge cycle tests, the battery achieved a stable cycle time of over 5000 hours, and the polarization curve did not exhibit any drastic fluctuations or short-circuit signals due to dendrite penetration. At a standard current density of 1 mA / cm², the overpotential at the interface remained stable at around 60 mV, far lower than that of unmodified or conventionally coated battery systems (typically >550 mV), demonstrating its excellent electrochemical performance. Furthermore, characterization of the interface mechanism using XPS and TOF-SIMS electron microscopy revealed the formation of an inorganic-rich phase. In-depth analysis of the interface after cycling showed that the SEI film formed after cycling with the addition of lithium active host and oxides exhibited obvious inorganic-rich phase characteristics. The unmodified interface SEI was dominated by organic phases (such as alkyl lithium carbonate), with high impedance and poor mechanical strength, making it highly susceptible to gas generation and cracking. XRD characterization also proved the effectiveness of the lithium active host framework. As shown in the figure, after repeated lithium intercalation and deintercalation, the lithium active host film can be completely and stably transformed into a high lithium content phase, which participates in the uniform lithium intercalation process as an active layer, effectively alleviating the local current concentration on the lithium metal surface and eliminating the risk of short circuit.

[0044] Based on the test data for cycle stability, polarization overpotential, and critical current density in Table 1, the composite interface layer and all-solid-state battery prepared through Examples 1-7 have significant advantages and can effectively meet the high standards required by customers and the market.

[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A battery composite interface layer, characterized in that, It includes both a physical buffer layer and a chemical induction layer; The physical buffer layer is a metal active host composite film, comprising a metal active host material and a polymer binder coated on its surface; The chemically induced layer is a nanoscale metal oxide thin film; The active host material of the metal is any one or more of graphite, graphene, silicon suboxide, molybdenum dioxide, conductive carbon black, hard carbon, and carbon nanotubes. The nanoscale metal oxide is an oxide of any metal element from Group IIIA, Group IIB, or Group IVB of the periodic table.

2. The composite interface layer according to claim 1, characterized in that, The polymer binder is a fluorinated polymer material.

3. The composite interface layer according to claim 1, characterized in that, The mass ratio of the metal active host material to the polymer binder is (9-199):

1.

4. The composite interface layer according to claim 1, characterized in that, The thickness of the composite interface layer is 1-100 μm.

5. The composite interface layer according to claim 1, characterized in that, The thickness of the nanoscale metal oxide film is 0.5-10 nm.

6. The method for preparing the composite interface layer according to any one of claims 1-5, characterized in that, Includes either of the following two preparation methods: (1) The metal active host material is premixed with the polymer binder and subjected to shear fibrillation treatment to make the mixture fibrillated. Then, the metal active host composite film is obtained by hot rolling process. A nanoscale metal oxide film is deposited on the surface of the composite film to obtain the composite interface layer. (2) The metal active host material is premixed with the polymer binder and subjected to shear fibrillation treatment to make the mixture fibrillated. Then, the metal active host composite membrane is obtained by warm rolling process. A nanoscale metal oxide film is deposited on the surface of the solid electrolyte membrane. Then, the metal active host composite membrane and the solid electrolyte membrane with the deposited nanoscale metal oxide film are rolled together to obtain the composite interface layer.

7. The application of the composite interface layer according to any one of claims 1-5 in all-solid-state batteries, liquid batteries or semi-solid-state batteries.

8. An all-solid-state battery, characterized in that, It includes a metal anode, a solid electrolyte, and a composite interface layer as described in any one of claims 1-5 disposed between the two.